CORRELATIONS BETWEEN DENTAL OCCLUSION AND UPPER CERVICAL SPINE - Smaranda Buduru; Andreea Prigoana; Andreea Vălean; Manuela Manziuc; Simona Iacob; Cecilia Bacali; Andrea Chisnoiu; Mariana Păcurar; Marius Negucioiu (Romanian Society of Oral Rehabilitation, 2021)
Aim of the study This study aims to determine whether skeletal class and abnormal values of certain variables on cephalometry (cranio-vertebral angle, intervertebral functional spaces, the space between the anterior arch of the atlas and the anterior face of the odontoid process, the C2-7V line and the hyoid triangle) represent possible risk factors for the occurrence of muscle and joint dysfunction. Another objective is represented by the determination of a possible occlusal dysfunction pattern in patients with temporo-mandibular disorder. Material and methods Twenty patients with dysfunction and pain in the temporo-mandibular joint and masticatory muscles were included in the study (TMD group). Subsequently, the control group was chosen, which included 20 patients, who did not have joint and muscle damage, but who had occlusion disorders. In order to collect the data, the patient's file was used, with records on both static and dynamic occlusion and also the data regarding the analysis of the muscles and the temporomandibular joint. Rocabado cephalometric analysis was used to evaluate cervical spine parameters. In order to determine the skeletal class, the Steiner analysis was used. Results Seventy-five percent of patients in control group were class I, while in TMD group 40% of patients were class I, the others being uniformly divided between class II and III. The mean value of the cervical functional space in C0-C2 area was lower in TMD group compared to control group, while in C1-C2 area presented equal values for both groups. Following the Fisher test analysis of the relationship of the C2-7V line and the hyoid triangle, no statistically significant association was detected between them and groups (p = 1; p = 0.305). Conclusions Skeletal class II is a risk factor for TMD. There is no statistically significant correlation between the values of the variables determined by the Rocabado cranio-cervical cephalometric analysis, and the occurrence of TMD. No pattern has been identified between static occlusion and TMD. Nonfunctional dynamic occlusion does not represent a risk factor for TMD development.